Carrier density and light helicity dependence of photocurrent in mono- and bilayer graphene. (15th October 2018) - Qian, X; Cao, B; Wang, Z; Shen, X; Soci, C; Eginligil, M; Yu, T
Abstract: Helicity-dependent photocurrent in monolayer graphene has been the subject of intense debate, and was recently ascribed to photon drag and circular photogalvanic effects. Unlike inversion symmetric monolayer graphene with no band gap, the most stable case of two-layer graphene, AB-stacked bilayer graphene, has broken inversion symmetry and can have a band gap upon electrical gating. Here we report the experimental determination of the photocurrent response of mono- and bilayer graphene as a function of light polarization, as well as carrier density and polarity. The mono- and bilayer graphene data show qualitative features in common with the photocurrent contribution that is expected to arise from the photon drag effect. On the other hand, the photocurrent due to the circular photogalvanic effect in bilayer (monolayer) graphene has asymmetric (symmetric) dependence on carrier density, which is attributed to particle-hole asymmetry.